Isolation of Hydrolytic Bacteria from Black Glutinous Rice Wash Water - Indra Adi Wira Prasetya; Elsa Mega Suryani; Rizka Kusuma Ningrum (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
Natural sources for hydrolytic enzymes produced by bacteria in demand in industry were increased. Hydrolytic bacteria can be found in agricultural and household waste, like black glutinous wash water. This study aims to identify and evaluate the presence and hydrolytic potential of bacteria in washing waste from fermented black glutinous rice. Fermented black glutinous rice washing water was used as the sample for bacterial isolation. The obtained isolates were screened for hydrolytic activity using modified Bushnell–Haas Agar supplemented with specific substrates to assess cellulolytic, amylolytic, and pectinolytic activities. Hydrolytic activity was expressed as a hydrolytic index to determine the most potent isolate, which was subsequently identified at the molecular level. A total of eight bacterial isolates were successfully obtained, among which one isolate, designated NKH4, showed the highest hydrolytic potential based on screening results. Molecular identification revealed that NKH4 is closely related to Bacillus tequilensis, with a similarity value of 97.96%. This species has previously been reported to produce various hydrolytic enzymes. The selected isolate NKH4 exhibited a qualitative hydrolytic index of 0.89, demonstrating its ability to hydrolyze starch, cellulose, and pectin. Therefore, NKH4, identified as Bacillus tequilensis, holds strong potential as a producer of hydrolytic enzymes and may serve as a promising candidate for further biotechnological applications.